Faktor-faktor yang mempengaruhi minat lansiamengunjungi Posyandu lansia - Rahmalia - Ningsih; Arneliwati - -; Widia - Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the factors affecting interest of the elderly in visiting  Elderly Integrated Health Centre. This study is a descriptive correlative study by using cross-sectional study design, and research methods using analytical survey. The study was conducted in 97 elderly people in the village Tuah Karya using the sampling method in purposive sampling. The measuring instruments used in the form of questionnaires and have tested the validity and reliability (r > 0,444). Analysis is used univariate and bivariate analysis using chi-square test. The study found that the factors affecting interest in the elderly visiting  elderly integrated health centre is knowledge (p value = 0,003), distance (p value = 0,397), and family support (p value = 0,001). Based on these result, it is recommended to the Health Center to make effort to improve the elderly posyandu through the promotion of the benefits posyandu, posyandu should be held in the middle of residential communities, and encouraged in elderly to increase its active role in activities and make posyandu as a necessity. Key words             : Distance, elderly, elderly posyandu, family support, interest,knowledge